2021
DOI: 10.1149/10101.0011ecst
|View full text |Cite
|
Sign up to set email alerts
|

Study of Methanol Electro-Oxidation on Thin Nickel Films by Sampled Current Voltammetry

Abstract: Nickel-based electrocatalysts have shown good catalytic activity for the electrochemical oxidation of alcohols in alkaline media, which has generated significant interest in using nickel films and nickel oxides in alcohol fuel cells. In this work, Ni films were deposited by the galvanostatic method on gold electrodes. The electrocatalytic activity for the electro-oxidation of methanol from these deposits was evaluated by cyclic voltammetry (CV) and sampled current voltammetry (SCV). Cyclic voltammetry measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the use of some elimination functions can lead to distortions of the irreversible current, which could manifest in other particular contributions. (9,10). Increasing the scan rate an order of magnitude had a marginal effect on the height of the methanol oxidation peak.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the use of some elimination functions can lead to distortions of the irreversible current, which could manifest in other particular contributions. (9,10). Increasing the scan rate an order of magnitude had a marginal effect on the height of the methanol oxidation peak.…”
Section: Resultsmentioning
confidence: 95%
“…The potential range on which methanol electro-oxidation takes place also favors other reactions that can proceed parallel to it, like oxygen evolution reaction (OER), and the formation of different NiOOH polymorphs (β and γ); all of them can play a role in the qualitative and quantitative characteristics of the voltammogram. Thus, separating the total current into its particular contributions can shed some light on the differences between the Ni films deposited by Salinas-Quezada (9). In this work, the oxidation of Type A and Type B Ni deposits, and the oxidation of methanol, were analyzed by ELSV to reveal mechanistic differences that could originate during the electrodeposition process.…”
Section: Ni(oh) 2 + Oh −mentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Salinas-Quezada et al observed a dependency between the applied deposition current applied and the electrocatalytic activity of nickel films. When lower deposition current values were applied, 22-33 µA, the electrocatalytic activity favored methanol oxidation, and with higher deposition currents, 38-66 µA, OER was favored [181]. This was attributed to changes in the growth regime because, during this stage, the geometric area defines the diffusion field of metallic ions.…”
Section: Future Perspectivesmentioning
confidence: 99%